Analisis Ekologi Sastra Pada Novel Suara Samudera Karya Maria Matildis Banda - Yongki Darmawan; I Nyoman Darma Putra; I G.A.A. Mas Triadnyani (Journal of Mandalika Literature, 2024)
Abstract: This research aims to determine the structure and ecological values contained in the novel. There are two theories used for this research, namely structural theory and literary ecological theory. The method used in this research is the library study method with advanced techniques in the form of note-taking and writing techniques. Then proceed by using informal methods and descriptive analytical methods to analyze the data. Next, the analysis results are presented using the description method. Based on the analysis carried out on the novel Suara Samudra, several things were found. First, in structural analysis which includes elements of characterization, plot and setting depicted in the novel Suara Samudra. Second, ecological values which include elements of natural ecology and cultural ecology in the novel Suara Samudra.